Antioxidant activities of anastatin A & B derivatives and compound 38c's protective effect in a mouse model of CCl4-induced acute liver injury. Issue 24 (14th April 2020) - Xiang, Cen; Cao, Menglin; Miao, Ai; Gao, Feng; Li, Xuzhe; Pan, Guojun; Zhang, Wenqiang; Zhang, Yongmin; Yu, Peng; Teng, Yuou
Abstract : Anastatins B derivative 38c both had good antioxidant activity in vitro and in vivo . Abstract : Anastatins A and B, two flavonoid compounds isolated from desert plant Anastatica hierochuntica, have protective activities for primary rat hepatocytes. Anastatins A and B, and their derivatives, were synthesized by our group previously. In this study, the antioxidant activity and cytotoxicity of these compounds were studied using chemical assessment methods, cell proliferation inhibition experiments, and cell oxidative damage models. The best compound, 38c, was used to study the hepatoprotection activity and mechanism by using a CCl4 -induced liver injury model in mice. The results show that most of these flavonoid compounds have good antioxidant activity and low cytotoxicity in vitro . Among them, the most potent compound was 38c, which exhibited a protective effect on CCl4 -induced hepatic injury by suppressing the amount of CYP2E1. These findings indicate that anastatin flavonoid derivatives have potential therapeutic utility against oxidative hepatic injury.